Managements of peritoneal dialysis patients during pandemic of novel coronavirus pneumonia virus - Luo Ji-cong; Liang Yan; Liu Da-shuang; Wang Ying (Linchuang shenzangbing zazhi)
In the context of managing new coronavirus pneumonia, peritoneal dialysis patients generally suffer from malnutrition and low immunity.Peritoneal dialysis patients should better gain a better understanding, implement household cares and guide the staff of peritoneal dialysis center to conduct close follow-ups during the pandemic.Specific guidelines were drafted and should be observed during hospitalizations and follow-ups after discharge.